2023
DOI: 10.3390/plants12040930
|View full text |Cite
|
Sign up to set email alerts
|

Plastomes of Garcinia mangostana L. and Comparative Analysis with Other Garcinia Species

Abstract: The two varieties of mangosteen (Garcinia mangostana L.) cultivated in Malaysia are known as Manggis and Mesta. The latter is preferred for its flavor, texture, and seedlessness. Here, we report a complete plastome (156,580 bp) of the Mesta variety that was obtained through a hybrid assembly approach using PacBio and Illumina sequencing reads. It encompasses a large single-copy (LSC) region (85,383 bp) and a small single-copy (SSC) region (17,137 bp) that are separated by 27,230 bp of inverted repeat (IR) regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 93 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…Regarding the initiation codon of ndhD, ACG is commonly used as an alternative to AUG in many land plants, but it can still be converted to a functional AUG initiator codon by RNA editing [103][104][105], probably depending on a molecular cofactor PPR protein CRR4 during transcription [106]. Additionally, GUG is also reported as an initiation codon of psbC and rps19 in other plants, such as Thalictrum (Ranunculaceae) [105], Garcinia (Clusiaceae) [107], Populus (Salicaceae) [108] and Betula platyphylla (Betulaceae) [109], but these two genes cannot be edited back to AUG. However, recent studies suggested that an important translation initiation signal, known as Shine-Dalgarno (SD) sequence, can interact with 3' end of the 16S rRNA and facilitate translation initiation from the GUG [109,110], which is responsible for expression of psbC and rps19 in chloroplast.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the initiation codon of ndhD, ACG is commonly used as an alternative to AUG in many land plants, but it can still be converted to a functional AUG initiator codon by RNA editing [103][104][105], probably depending on a molecular cofactor PPR protein CRR4 during transcription [106]. Additionally, GUG is also reported as an initiation codon of psbC and rps19 in other plants, such as Thalictrum (Ranunculaceae) [105], Garcinia (Clusiaceae) [107], Populus (Salicaceae) [108] and Betula platyphylla (Betulaceae) [109], but these two genes cannot be edited back to AUG. However, recent studies suggested that an important translation initiation signal, known as Shine-Dalgarno (SD) sequence, can interact with 3' end of the 16S rRNA and facilitate translation initiation from the GUG [109,110], which is responsible for expression of psbC and rps19 in chloroplast.…”
Section: Discussionmentioning
confidence: 99%
“…(e.g., salak) and Syzygyium spp. (e.g., java apple) (Blench, 2008; Larson et al, 2014; Lebot, 1999; Shaharudin et al, 2022; Thorogood et al, 2022; M. Wang et al, 2018; Warschefsky & von Wettberg, 2019; Wee et al, 2022; Wu, Terol, et al, 2018). Domestication of many of these fruit crops could reflect the pattern we have observed, whereby wild progenitors with small fruits were found in more mountainous areas and large fruit progenitors in the more productive wet lowlands.…”
Section: Discussionmentioning
confidence: 99%
“…borneensis , are genetically differentiated, or whether differences between them in morphological traits are due to phenotypic plasticity. Genome (Abu Bakar et al, 2016) and plastome (Wee et al, 2022) datasets of cultivated mangosteen are now available for reference for Single Nucleotide Polymorphism (SNP) calling. Analysis of both nrDNA and cpDNA markers in a large number of samples from across the region would enable inferences about several open questions: (i) patterns of genetic variation in mangosteen and its wild relatives; (ii) whether gene flow occurs between them, and whether any gene flow detected is unidirectional (from wild pollen donors to mangosteen), as expected from results of crossing experiments (Hambali & Natawijaya, 2016); (iii) whether mangosteen originated from numerous initial progenitors that arose from independent events of sexual reproduction.…”
Section: Synthesismentioning
confidence: 99%